Evaluation of Terminalia chebula Retz. Extract Against Caries-associated Bacteria as an Alternative Compound for Oral Care Products - Prompamorn, Piyanuch; Itsarasook, Khwunjit; Tanghiranra, Jitrawadee; Tripetch, Chanchai; Chantree, Kanlayaporn (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this study was to investigate the efficiency of Terminalia chebula Retz. fruit extract for further use as an active ingredient in oral care products. The quantification of major constituent, the antioxidant activity and antibacterial activity of an extract against Streptococcus mutans in both planktonic and biofilm form were measured. The results showed that ellagic acid was the major constituent of an extract and the amount of ellagic acid contained in the extract was 36.671 mg/g. The extract exhibit free radical scavenging activity with IC50 value of 0.44±0.01 mg/mL by DPPH assay. For antibacterial activity against S. mutans, T. chebula Retz. extract possess high inhibitory effect on S. mutans in both planktonic form and biofilm form. The MIC50 and MBC value of an extract against planktonic form of S. mutans were 0.47±0.28 and 6.25 mg/mL, respectively. For biofilm form of S. mutans, the extract has a high capability to preventing biofilm formation and eradicating the existing biofilm. The MBIC50 and MBEC50 of an extract against biofilm form of S. mutants were 4.47±0.32 and 9.64±0.39 mg/mL, respectively